Analysis of tera gymnastic as an intervention of acute pain nursing problems in elderly families with hypertension - Arita Murwani; Anna Nur H; Fatimah Sari (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Background: One of the problems that occurs in the elderly is hypertension. Hypertension has many symptoms, including dizziness, fatigue, difficulty sleeping, and one of them is acute pain in the nape of the neck. In treating pain, there are two methods of treatment, namely pharmacological techniques and non-pharmacological, one of the non-pharmacological treatments is tera exercise. Terra exercise is an alternative way to reduce pain. Objective: To analyze the implementation of acute pain nursing care for elderly families who experience hypertension problems in Trayeman Pleret Hamlet, Bantul. Method: This research method uses descriptive methods. The approach used is a case study with the management of one case using a nursing care process approach involving elderly families who experience acute pain nursing problems with hypertension. This research with quantitative method Results: After performing tera exercises three times for ± 60 minutes, participants said the pain had decreased from a pain scale of 5 to 2. Conclusion: The application of tera exercise can reduce the problem of acute pain nursing in elderly families with hypertension. The benefits for nursing with the discovery of tera exercise have become an innovation for the implementation of nursing care for elderly patients.